2007
DOI: 10.1111/j.1440-1746.2006.03373.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury induced by a Japanese herbal medicine, sairei‐to (TJ‐114, Bupleurum and Hoelen Combination, Chai‐Ling‐Tang) R1

Abstract: The case is reported of a man who showed acute hepatitis with jaundice after he was given a Japanese herbal medicine, sairei-to (TJ-114, Bupleurum and Hoelen Combination, Chai-Ling-Tang). Unusually, the component thought to be responsible for the observed drug-induced liver injury was able to be identified. Lymphocyte migration inhibition testing indicated that the tuber of the perennial herbage Pinellia ternate was the causative agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Chai Ling Tang), which is included in a blend of two TCM products, Xiao Chai Hu Tang and Wu Ling San Wan, and experienced liver injury [166,167]. Among the Sairei To ingredients are Alisma , Atractylis , Bupleurum , Cinnamomum , Ginseng , Glycyrrhiza , Pinellia , Polyporus , Poria , Scutellaria , Zingiber and Zizyphus .…”
Section: Narratives Of Tcm Hili Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chai Ling Tang), which is included in a blend of two TCM products, Xiao Chai Hu Tang and Wu Ling San Wan, and experienced liver injury [166,167]. Among the Sairei To ingredients are Alisma , Atractylis , Bupleurum , Cinnamomum , Ginseng , Glycyrrhiza , Pinellia , Polyporus , Poria , Scutellaria , Zingiber and Zizyphus .…”
Section: Narratives Of Tcm Hili Casesmentioning
confidence: 99%
“…Among the Sairei To ingredients are Alisma , Atractylis , Bupleurum , Cinnamomum , Ginseng , Glycyrrhiza , Pinellia , Polyporus , Poria , Scutellaria , Zingiber and Zizyphus . Several possible offending agents are considered, including Pinellia ternate [166] and other components of Sairei To [167]. …”
Section: Narratives Of Tcm Hili Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that Saireito occasionally causes side effects such as immunodeficiency, gastro-duodenal ulcer and osteoporosis that are often associated with long-term administration of corticosteroids 55 . Drug-induced pneumonitis and drug-induced acute hepatitis have been also reported with Saireito treatment 56,57 . However, the side effects of these TCHM are usually underreported in clinical trials.…”
Section: Introductionmentioning
confidence: 92%
“…According to the Chinese pharmacopoeia, the clinical safe dosage of RB prescriptions ranged from 3 g/day to 10 g/day, based on 70 kg body weight. However, based on accumulating evidence, RB probably contributes to hepatotoxicity, particularly overdose-induced acute liver injury and accumulation-related hepatotoxicity [811]. Patients using Xiao-Chai-Hu-Tang and Long-Dan-Xie-Gan-Tang or Chinese herbal products containing more than 19 g of RB might were recently shown to have an increased risks of liver injury [3].…”
Section: Introductionmentioning
confidence: 99%